An Epidemiological Study of Snake Bite Cases in Children of Nepal - Joshi, DD (Journal of Nepal Paediatric Society, 2010)
Introduction: Snakebite is common in the Terai region of Nepal. Injury and mortality of humans due to Snake envenomation is a serious pubic health problem in Southeast Asia and Nepal. It has been thought that at least 50,000 people in the region die of snake bites (this includes India, Bangladesh and Nepal and Pakistan) per year. There are abundant venomous snakes present in the region. Studies in Nepal have identified 4 species of snake responsible for the majority of fatal bites. These are the Indian cobra (Naja naja), common krait (Bungaris caeruleus) Russell's viper (Viper ressellii) and greenpit viper. The incidence of snakebite varies from 300-500 bites per 100,000 human populations in forested regions to 50-100 bites per 100,000 in Sahara. Objective: To study the epidemiology of snakebite in the endemic regions of the terai, to analyse the morbidity and mortality data of snakebite cases in children for the year 2008. Method: National Zoonoses and Food Hygiene Research Centre (NZFHRC) started collection of secondary and primary information on snakebite cases in children recorded and reported by different media and hospitals, health post in Nepal during the year 2008. The data had been compiled, tabulated and analysed. This is the regular surveillance study carried out on snakes in general and venomous snakebite human cases recorded in Nepal. The team visited in 6 mid, hill districts and 24 terai districts of Nepal. Results: Total snakebite cases in children were 540 during the year 2008. Of which 10 cases were from six mid hill districts and 530 were from 24 terai and inner terai districts of Nepal. Total morbidity was 406 (75.19%) and mortality 134 (24.81%). Seasonal incidence of snakebite cases recorded in Bheri zonal hospital and medical college Banke district. Highest morbidity were recorded during the month of Jestha (May) to Aswin (August). Morbidity 12 (25%) and mortality 3 (20%) were recorded in the month of May/June 2008. Conclusions: Snakebite cases in children and deaths were recorded and reported along with adult cases of snakebite. Total adult cases were 2190 of which children were 540 (24.66%) during the year 2008. This means that about 25% of all cases of snakebites were seen in children every year in the endemic areas of snakes. Mass awareness school education programme about snakebite especially in endemic area of terai and inner districts should be advocated regularly so that parents along with children will take necessary precautions. Key words: Snakebite; Epidemiological surveillance; Anti-snake venom; Poisonous and envenomation. DOI: 10.3126/jnps.v30i3.3915 J Nep Paedtr Soc 2010;30(3):135-140